2004
DOI: 10.1197/j.aem.2003.09.019
|View full text |Cite
|
Sign up to set email alerts
|

An Educator's Guide to Teaching Emergency Medicine to Medical Students

Abstract: Thereis a need for every medical school graduate to handle emergencies as they arise in the daily practice of medicine. Emergency medicine (EM) educators are in a unique position to provide students with basic life support skills, guidance in assessing the undifferentiated patient, and exposure to the specialty of EM during all years of medical school. Emergency physicians can become involved in a variety of education experiences that can supplement the preclinical curriculum and provide access to our specialt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 13 publications
1
12
0
7
Order By: Relevance
“…Clinical bedside teaching, problem-based learning groups, case conferences, simulation, and self-directed learning have all been cited as suggested settings for education in the EM clerkship, but evidence-based best practices for how to deliver the curricular content of an EM clerkship have yet to be formalized (4,15,16). It is logical to believe that some combination of clinical (actual or simulated) and didactic modalities may be ideal as suggested by previous literature (16,17). Our results are in line with the work of Debehnke who showed that readings augmented with case conferences improved student knowledge (18).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Clinical bedside teaching, problem-based learning groups, case conferences, simulation, and self-directed learning have all been cited as suggested settings for education in the EM clerkship, but evidence-based best practices for how to deliver the curricular content of an EM clerkship have yet to be formalized (4,15,16). It is logical to believe that some combination of clinical (actual or simulated) and didactic modalities may be ideal as suggested by previous literature (16,17). Our results are in line with the work of Debehnke who showed that readings augmented with case conferences improved student knowledge (18).…”
Section: Discussionsupporting
confidence: 90%
“…The increase in test scores seen in the DL group may not only be reflective of increased knowledge but also improved critical thinking skills, which can be taught during problem-based learning sessions (17). In this instance, students bring their individual clinical experiences with similar cases to the table for the case conference.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda, a construção destas matrizes levou em conta sua aplicabilidade em diferentes propostas de projetos pedagógicos. A opção por um modelo de ensino orientado por competências encontrou respaldo em algumas das referências bibliográficas usadas na execução do trabalho 14,[19][20][21][22][23] .…”
Section: Discussionunclassified
“…Tais referências foram utilizadas na execução do presente trabalho, para definição final das competências a serem adquiridas durante o estágio de urgências clínicas, considerando os níveis secundário e terciário da atenção à saúde 14,15,[19][20][21][22][23] .…”
Section: Metodologiaunclassified
“…Coates [11] has suggested a similar scheme for the teaching of emergency medicine to Californian medical students in their senior-year rotation.…”
mentioning
confidence: 99%